Agrupamento de espécies madeireiras da amazônia em função da densidade básica e propriedades mecânicas - Catanhede do Nascimento, Claudete; Garcia, José Nivaldo; Diáz, Maria del Pilar (Instituto de Ecología, A.C., 2016)
This work is the result of a multivariate analysis of 87 A mazon wood species, as function of their basic density and their mechanical properties. Five different groups of species were identified. Within each group, the species showed similar properties. These species present new alternatives to replace the tradicional A mazon wood species.